AKAD PEMBIAYAAN MURABAHAH KENDARAAN BERMOTOR PERUSAHAAN PEMBIAYAAN PT. CIMB NIAGA AUTO FINANCE - SYARIFAH SINAGA (Lex Renaissance, 2016)
AbstractMurabaha Contract For Financing Vehicle Purchase In PT. CIMB Niaga Auto Finance Company.  Murabaha is a financing product which is a sale and purchase or sale and purchase agreement by declaring main cost of the goods and make a profit (margin) which has been agreed by the seller and the buyer. Sharia banking and finance institution have commonly used murabaha financing in their activities. The aim of this research are to depict on how murabaha financing product is conducted by a non sharia financing institution  in this case PT CIMB Niaga Auto Finance. The result of this research hopely can describe the differences between murabaha act which applying sharia principles compare to conventional financing; the state of  Power of Attorney on making fiduciary act that perform the sharia banking principles; and legal standing of mutual agreement between the dealer and financing company.Key word: murabahah, pembiayaan kendaraan.